Neural manifestation of L2 novel concept acquisition from multi-contexts via both episodic memory and semantic memory systems - Xu, Shuang; Wang, Hailing; Li, Shouxin; Ouyang, Guang (Frontiers in Psychology, 2024)
Neur al manifestation of L2 novel concept acquisition fr om multi-contexts via both episodic memor y and semantic memor y systemsThis study aims to examine the process of L2 novel word learning through the combination of episodic and semantic memory, and how the process differs between the formation of thematic and taxonomic relations. The major approach adopted was observing the neural effects of word learning, which is manifested in the N400 from event-related potentials (ERPs). Eighty-eight participants were recruited for the experiment. In the learning session, L2 contextual discourses related to novel words were learned by participants. In the testing session, discourses embedded with incongruous and congruous novel words in the final position were used for participants to judge the congruency which affected the N400 neural activity. The results showed that both recurrent and new-theme discourses elicited significant N400 effects, while taxonomic sentences did not. These results confirmed the formation of episodic and semantic memory during L2 new word learning, in which semantic memory was mainly supported by thematic relations.